Społeczne podstawy poznania i rozwoju – konstruktywizm społeczno-kulturowy Lwa S. Wygotskiego. Nowe odczytania, rekonstrukcje, tropy epistemologiczno-metodologiczne - Ewa Filipiak (Problemy Wczesnej Edukacji)
The original concept, theory-method of Lev S. Vygotsky, the innovative nature of his views allows to adopt new theoretical and methodological tools to describe the process of development and learning of a child, reconstruct what is happening in the classroom and in the students’ minds. For many years the interest in Vygotsky’s concept has been experiencing a renaissance all over the world, also in Poland. The cognitively sophisticated concept has original terminology. Unfortunately, in the discourses, frequent borrowings and loose usage of terms have been observed, as well as the reproduction of Vygotsky’s words without discovering the meaning or giving them a deeper meaning. As a consequence, this brings the risk of distortion of the idea and the apparent change of school culture, its opening to a new quality (socio-cultural constructivism). In this article I share my reflection on: research and Research and Development (R&D) activities based on the theory-method of L.S. Vygotsky, applying his ideas to pedagogical research, and educational implications for changing everyday teaching practice.